Exploration of Crotalaria spectabilis Stem Alkaloids as Green and Environmentally Benign Corrosion Inhibitor Against Mild Steel in 1 M H2SO4 Medium - Bohara.R, Dilip Singh; Bist, Birendra Bahadur; Dhakal, Kamala; Aryal, Sabin; Subedee, Anup; Shrestha, Ram Lal Swagat; Bhattarai, Deval Prasad; Oli, Hari Bhakta (Amrit Research Journal, 2024)
The study of corrosion inhibition using plant extracts as environmentally friendly inhibitors is an emerging area of research. In this work, alkaloids were successfully extracted from the stems of Crotalaria spectabilis by a solvent extraction method. Qualitative characterization of extracted alkaloids was performed using chemical test methods and the Fourier Transformed Infrared Spectroscopy (FTIR) technique. The alkaloids extracted were tested as corrosion inhibitors on mild steel (MS) exposed to 1.0 M H2SO4, and their effectiveness was evaluated using gravimetric and electrochemical techniques. The study used the weight loss method to examine how inhibitor concentration, immersion time, and working temperature affect corrosion inhibition efficiency. The results showed a maximum inhibition efficiency of 90.38% for mild steel (MS) immersed in a 1000 ppm alkaloid solution for 6 hours at 25 °C. Similarly, polarization measurements indicated a maximum inhibition efficiency of 92.86%. The alkaloids demonstrated effective inhibition efficiency at temperatures up to 45 °C. The studies on adsorption isotherm, activation energy, and free energy of adsorption suggested that the alkaloids follow the Langmuir adsorption isotherm through physisorption. Overall, the findings indicate that the extracted alkaloids have the potential to serve as environmentally friendly inhibitors for mild steel corrosion.